Recovery Ice Stream Subglacial Hydrology Simulation - Dow, Christine; Werder, Mauro (Zenodo, 2018)
These data are outputs from GlaDS subglacial hydrology model applied to Recovery Ice Stream, East Antarctica. These outputs are used to analyse subglacial lake growth and drainage rates along with channel growth and variability in water pressure. : netcdf file naming conventions follow parameters listed in Werder et al (2013) and Dow et al (2016).